Estratégias de aprendizagem na aula de língua estrangeira: um estudo com formandos em Letras - Silva, Gisvaldo Araújo (2006)
Foreign language (henceforth FL) learning process plays an important role as a knowledge construction facilitator when it aims at developing the learner s ability to communicate through this language. Based on this assumption, researches in Applied Linguistics have investigated FL learning. Among the resources that contribute to language learning, the literature has identified a language learning strategies (henceforth LS) taxonomy a set of procedures that can help students to develop actions, take attitudes and decisions on what to do to enhance learning in terms of cognition, metacognition, compensation, affectivity and social interaction (Oxford, 1990; Figliolini, 2004). These LS may be used by students or taught them more or less consciously, depending on the teaching approach. This research intends to investigate LS use in a Portuguese/English language studies undergraduate course last two terms. Thus, this research main goals are: a) identifying LS used by students in some moments of communicative activities during different classroom tasks; b) identifying the most used LS in this context; c) identifying which ones seem to be better off to students communicative competence development or to a given task accomplishment; and d) analyzing the possible relationships among the teacher s approach, peers interaction and these LS use. In order to do that, first 12 classes from each of the two terms observed were recorded.After that the 6 classes from each of two groups that seemed more representative of these classrooms dynamics were chosen. Then these classes were watched a couple of times and all the moments which LS were identified were transcribed. Later on the transcript was reviewed and all the LS identified were tabulated. Finally the LS use was analyzed in order to find out whether they enhanced learning in terms of communication and grammatical adequacy. At the same time the possible relations between learning context and the appropriateness of those LS used were analyzed.Findings show that although students use a great number of LS, they do not always pay attention to their efficiency or to their adequacy. Therefore, it seems interesting that teachers not only focus on their content area but also on how students respond to their teaching approach and how they deal with their own learning. So teachers should help the student to be self-conscious about his/her own learning. As a result, the learner might be able to develop the ability of selecting, using and evaluating the most appropriate LS for his/her needs and consequently he/she will enhance his/her FL communicative competence.